3х-у=3, 2. 2х-3у=1, 3. 2х+у=1, 4. х+у=6,
3х-2у=0. 3х+у=7. 5х+2у=0. 5х-2у=9.
5. х+5у=7, 6. х+у=7, 7. 4х-3у=-1, 8. х+2у=-2,
3х+2у=-5. 5х-7у=11. х-5у =4. 3х-у=8.
9. 2х-5у=-7, 10. х-у=3, 11. 3х-5у=16, 12. 2х+3у=-7,
х-3у=-5. 3х+4у=2. 2х+у=2. х-у=4.
13. 2х+5у=-7, 14. х-3у=8, 15. 2х-3у=5, 16. х-4у=-1,
3х-у=15. 2х-у=6. х-6у=-2. 3х-у=8.
17. 5х-4у=12, 18. 6х+у=5, 19. 2х-3у=11, 20. х-6у=-2,
х-5у=-6. 2х-3у=-5. 5х+у=2. 2х+3у=11.
21. 3х-2у=16, 22. 2х+3у=3, 23. 4х-2у=-6, 24. 3х+2у=8,
4х+у=3. 5х+6у=9. 6х+у==11. 2х+6у=10.
25. 5х+у==14, 26. 3х-2у=5, 27. х+4у=7, 28. 2х-3у=5,
3х-2у=-2. 2х+5у=16. х-2у=-5. 3х+2у=14.
29. х-2у=7, 30. 4х-6у=26, 31. х+3у=7, 32. 8х+3у=-21,
х+2у=-1. 5х+3у=1. х+2у=5. 4х+5у=-7.
33. х-2у=8, 34. 8х+2у=11, 35. 2х-у=13, 36. 7х+3у=1,
х-3у=6. 6х-4у=11. 2х+3у=9. 2х-6у=-10.
37. 2х+3у=10, 38. 3х-2у=5, 39. 2х+у=-5, 40. 2х+3у=1,
х-2у=-9. 5х+4у=1. х-3у=-6. 6х-2у=14.
ответ: 120*a^4*b^9*c^2
Решаем по действиям:1. 4*2.5=10 X2.5 _ _4_ 10 2. a*a^2=a^3 a*a^2=a^(1+2) 2.1. 1+2=3 +1 _2_ 33. (-10*a^3*b^3)*(-4*a*b^3)=-10*a^3*b^3*(-4*a*b^3)4. 10*a^3*b^3*(-4*a*b^3)=-10*a^3*b^3*4*a*b^35. 10*4=40 X10 _4_ _ 406. a^3*a=a^4 a^3*a=a^(3+1) 6.1. 3+1=4 +3 _1_ 47. b^3*b^3=b^6 b^3*b^3=b^(3+3) 7.1. 3+3=6 +3 _3_ 68. -(-40*a^4*b^6)=40*a^4*b^69. 40*3=120 X40 _3_ _ 12010. b^6*b^3=b^9 b^6*b^3=b^(6+3) 10.1. 6+3=9 +6 _3_ 9
Решаем по шагам:1. (-10*a*b^3*a^2)*(-4*a*b^3)*c^2*3*b^3 1.1. 4*2.5=10 X2.5 _ _4_ 10 2. (-10*a^3*b^3)*(-4*a*b^3)*c^2*3*b^3 2.1. a*a^2=a^3 a*a^2=a^(1+2) 2.1.1. 1+2=3 +1 _2_ 33. (-10*a^3*b^3*(-4*a*b^3))*c^2*3*b^3 3.1. (-10*a^3*b^3)*(-4*a*b^3)=-10*a^3*b^3*(-4*a*b^3)4. (-(-10*a^3*b^3*4*a*b^3))*c^2*3*b^3 4.1. 10*a^3*b^3*(-4*a*b^3)=-10*a^3*b^3*4*a*b^35. (-(-40*a^3*b^3*a*b^3))*c^2*3*b^3 5.1. 10*4=40 X10 _4_ _ 406. (-(-40*a^4*b^3*b^3))*c^2*3*b^3 6.1. a^3*a=a^4 a^3*a=a^(3+1) 6.1.1. 3+1=4 +3 _1_ 47. (-(-40*a^4*b^6))*c^2*3*b^3 7.1. b^3*b^3=b^6 b^3*b^3=b^(3+3) 7.1.1. 3+3=6 +3 _3_ 68. 40*a^4*b^6*c^2*3*b^3 8.1. -(-40*a^4*b^6)=40*a^4*b^69. 120*a^4*b^6*c^2*b^3 9.1. 40*3=120 X40 _3_ _ 12010. 120*a^4*b^9*c^2 10.1. b^6*b^3=b^9 b^6*b^3=b^(6+3) 10.1.1. 6+3=9 +6 _3_ 9